Use of Augmented Random Search Algorithm for Transmission Line Control in Smart Grids - A Comparative Study with RNA-based Algorithms - Rufino, Antonio B. S.; Saraiva, Filipe (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2023: Anais do XX Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2023.234524, 2023)
Due to climate change challenges, countries are diversifying their energy sources to reduce carbon emissions and adopt cleaner alternatives. However, integrating these new energy sources into existing power grids poses challenges, such as increased intermittency. Prior studies have shown that active control of the power grid's topology can address these issues. This research aims to demonstrate the effectiveness of the Augmented Random Search (ARS) algorithm as a faster alternative to neural network-based reinforcement learning algorithms. The ARS algorithm can achieve comparable results to neural networks in significantly less time, enabling a broader range of tests and reducing computational training costs.